Determining future location of malls in urban growth centers a case study of Tuguegarao City in Cagayan Province - Lavadia, Grinda R.; Dina C. Magnaye (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2017)
In the Philippines, malls have been expanding at an unprecedented pace. Due to competition among private developers for the best possible sites for mall development, location is considered crucial in mall development. Thus, it is deemed essential to determine the factors considered by private developers in selecting sites for mall development, which is, in turn, informed by factors considered by mall customers in choosing locations when shopping for goods. The analysis used in this study to locate mall development was done both at the national and local levels, with the latter focusing on the City of Tuguegarao as the case study area. At the national level, developers usually selected preferred provinces for their proposed mall expansion. Potential cities from the list of candidate provinces were chosen based on factors such as population size, extent and diversity of economic activities, presence of LGU incentives, and land availability, among others. In Tuguegarao City, the target market mainly considered proximity to the mall when shopping for goods and availing of services. Shoppers preferred shorter travel time when going to the malls. This supports the finding that the area near the city center is the ideal location for mall development. The factors that were considered by both the developer and the target market include population, accessibility and convenience. developers study demographics, economic activities, accessibility and intrinsic factors of an area such as the size and shape of the land for potential mall location. The target market looks for mall locations that are accessible from their residence or workplace. LGU participation was found to be often left out by the developers during the mall development selection process. The LGU were involved only when a site had already been selected for mall development. Further, the LGUs do not explicitly include mall location in planning or policymaking; and only designate commercial zones in the land use plans and in the zoning ordinance. The study recommends the following: a) conduct of an in-depth study on mall habits of the target market and accessibility; b0 integration of mall location in urban planning and LGU zoning; c) provision by the LGU of incentives to mall developers and support system to include pedestrian overpass, efficient traffic light system, and trained traffic management personnel; and c) conduct of studies on factors affecting location of smaller malls and their carrying capacity.
Thesis (Master of Arts in Urban and Regional Planning)--University of the Philippines Diliman, June 2017.
Keywords: Shopping malls -- Philippines -- Tuguegarao City (Cagayan) -- Planning; Building sites -- Philippines -- Tuguegarao City (Cagayan) -- Planning; Cities and towns -- Philippines -- Tuguegarao City (Cagayan); Store location -- Philippines -- Tuguegarao City (Cagayan) -- Planning